2020
DOI: 10.33631/duzcesbed.740550
|View full text |Cite
|
Sign up to set email alerts
|

Siirt İlinde Yüksek Hepatit Delta Antikoru Sıklığı

Abstract: Eş zamanlı hepatit delta virüs (HDV) enfeksiyonu varlığı kronik hepatit B (KHB) ilişkili karaciğer hastalığının seyrini olumsuz yönde etkilemektedir. Bu çalışmada Siirt ilinde hepatit B virusu (HBV) ile kronik olarak enfekte olan hepatit gelişmiş ve gelişmemiş olgularda delta antikoru (anti-HDV) sıklığının belirlenmesi ve HDV koenfeksiyonu varlığının klinik etkilerinin irdelenmesi amaçlanmıştır. Gereç ve Yöntemler: Bu retrospektif kesitsel çalışmaya Şubat 2017-Şubat 2018 tarihleri arasında Siirt Devlet Hastane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…The quality effects model estimates were comparable. Of these six studies, three were from Eastern Turkey [8 , 9] , two were from Western Turkey [10 , 11] and one was from Central Turkey [12] . Interestingly, both studies from Western Turkey were from the very same hospital in Izmir [10 , 11] .…”
Section: Resultsmentioning
confidence: 99%
“…The quality effects model estimates were comparable. Of these six studies, three were from Eastern Turkey [8 , 9] , two were from Western Turkey [10 , 11] and one was from Central Turkey [12] . Interestingly, both studies from Western Turkey were from the very same hospital in Izmir [10 , 11] .…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, functional kidney disorders occur. Functional disorders of the kidneys are associated with increased serum urea and creatinine levels (Uzlu et al 2010, Başer and Civelek 2013, Bal 2019, Eroğlu and Kırbaş 2020. Similar to literature reports, in the present study, when compared to the healthy controls, the diseased cattle were found to present with increased serum urea and creatinine levels (P<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Doğu Anadolu Bölgesinde 2006-2021 yıllarında yapılan çalışmalar incelendiğinde, bu değerin %3.2-%45.5 gibi geniş bir aralıkta olduğu; bununla birlikte, son çalışma verilerine göre doğu bölgelerimizde HDV'nin halen büyük bir sağlık sorunu olmaya devam ettiği anlaşılmaktadır (5,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) . Ailelerin zorlu iklim ve coğrafi koşullar gibi nedenlerle aşı konusunda gereken hassasiyeti gösterememesi, kalabalık aile yapısı nedeniyle aile içi bulaş, düşük sosyoekonomik düzey, bölgenin dış göç alması HDV prevalansının yüksek seyretmesinin nedenleri arasında olabilir.…”
Section: Discussionunclassified